1998
DOI: 10.1124/mol.53.4.602
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of c-Jun NH2-Terminal Kinase Activation and c-Jun in the Induction of Apoptosis by the Ether Phospholipid 1-O-Octadecyl-2-O-methyl-rac-glycero-3-phosphocholine

Abstract: The ether phospholipid 1-O-octadecyl-2-O-methyl-rac-glycero-3-phosphocholine (ET-18-OCH3; edelfosine) is a potent inducer of apoptosis in human tumor cells. We show that ET-18-OCH3-induced apoptosis is associated with activation of the c-Jun NH2-terminal kinase (JNK) signaling. The addition of ET-18-OCH3 to distinct human leukemic cells (HL-60, U937, and Jurkat), which undergo rapid apoptosis on treatment with ET-18-OCH3, induced a dramatic and sustained increase in the of c-jun mRNA level that was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0
9

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 36 publications
8
83
0
9
Order By: Relevance
“…Previous studies have shown a critical role for persistent JNK activation in EDLF-mediated apoptosis (Gajate et al, 1998;Ruiter et al, 1999), EDLF being a rapid and potent JNK activator (Gajate et al, 1998;Ruiter et al, 1999) as well as a strong inducer of c-jun upregulation in leukemic cells (Mollinedo et al, 1994).…”
Section: Apoptosis Chaperoning Role Of Hsp90 In Lipid Rafts T Nieto-mmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have shown a critical role for persistent JNK activation in EDLF-mediated apoptosis (Gajate et al, 1998;Ruiter et al, 1999), EDLF being a rapid and potent JNK activator (Gajate et al, 1998;Ruiter et al, 1999) as well as a strong inducer of c-jun upregulation in leukemic cells (Mollinedo et al, 1994).…”
Section: Apoptosis Chaperoning Role Of Hsp90 In Lipid Rafts T Nieto-mmentioning
confidence: 97%
“…Because Hsp90 and JNK were recruited in lipid rafts, and EDLF-induced apoptosis is dependent on sustained JNK activation (Gajate et al, 1998;Ruiter et al, 1999), we hypothesized that Hsp90 might interact with unusual client proteins when present in a new scenario, favoring apoptosis and JNK activation. Persistent JNK activation is associated with apoptosis, whereas transient JNK activation is linked to proliferating and differentiating responses (Chen et al, 1996).…”
Section: Hsp90 Interacts With Jnk Upon Their Recruitment Into Lipid Rmentioning
confidence: 99%
See 1 more Smart Citation
“…At 20 mM, we found that ALPs ranked edelfosine>perifosineberucylphosphocholineXmiltefosine in their capacity to induce apoptosis in the pancreatic BxPC-3, Capan-2, CFPAC-1 and HuP-T4 cancer cells (Figure 1b). We included in our analysis the structurally related inactive edelfosine analog 1-O-octadecylrac-glycero-3-phosphocholine (ET-18-OH) (Mollinedo et al, 1997;Gajate et al, 1998), in which the methoxy group in the sn-2 position was replaced by an OH group. We found that, unlike edelfosine and perifosine, the other ALPs rendered low figures of apoptosis similar to ET-18-OH (Figure 1b).…”
Section: Induction Of Apoptosis By Edelfosine and Other Alps In Humanmentioning
confidence: 99%
“…Protein kinase assays were carried out using a fusion protein between glutathione S-transferase and c-Jun (amino acids 1-223) as a substrate of JNK, as previously described (Gajate et al, 1998(Gajate et al, , 2000a.…”
Section: Solid-phase Jnk Assaymentioning
confidence: 99%